PENGARUH PANDEMI COVID-19 TERHADAP ANGKA KEPENDUDUKAN DI INDONESIA - Tiara Maharani Ramadhanti; Nunung Nurwati (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2021)
Now the world is facing a COVID-19 pandemic and this has also happened in Indonesia. The impact of the COVID-19 pandemic is very detrimental to humanity because it takes the lives of many humans and of course impacts also on various aspects of life such as economic, social and others. The main highlight of the corona virus outbreak is that many people die from transmission of this virus. very quickly and even those who are susceptible to infection at the age of 30 and older. The emergence of the COVID-19 pandemic contributed to the high rate of spread and the fatality rate. Based on the results of the 2015 Intercensal Population Survey (SUPAS) the population of Indonesia in 2020 was 269.6 million people and based on age group, the number of productive age population (15-65 years) reached 185.22 million people or around 68.7% of the total population. Thus the population in Indonesia with a productive age is threatened to decrease with a drastic increase in mortality, but it cannot be denied that the existence of a COVID-19 pandemic can also have an impact on increasing fertility in Indonesia due to this unstable economic aspect which impacts 1.2 million job cuts. more workers from the formal and informal sectors and a falling rupiah exchange rate so that the loss of employment has an impact on the difficulty of paying for life as well as education so that early marriage can occur because this pandemic has a major impact on aspects of life and population figures in Indonesia.